Beispiel Nr: 03
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 9 x -2 y =5\\ 5 x -2 y = 1 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} \\I \qquad 9 x -2 y =5\\ II \qquad 5 x -2 y = 1 \\ I \qquad 9 x -2 y =5 \qquad / \cdot5\\ II \qquad 5 x -2 y = 1 \qquad / \cdot\left(-9\right)\\ I \qquad 45 x -10 y =25\\ II \qquad -45 x +18 y = -9 \\ \text{I + II}\\ I \qquad 45 x -45 x-10 y +18 y =25 -9\\ 8 y = 16 \qquad /:8 \\ y = \frac{16}{8} \\ y=2 \\ \text{y in I}\\ I \qquad 9 x -2\cdot 2 =5 \\ 9 x -4 =5 \qquad / +4 \\ 9 x =5 +4 \\ 9 x =9 \qquad / :9 \\ x = \frac{9}{9} \\ x=1 \\ L=\{1/2\} \end{array} & \begin{array}{l} \\I \qquad 9 x -2 y =5\\ II \qquad 5 x -2 y = 1 \\ I \qquad 9 x -2 y =5 \qquad / \cdot\left(-1\right)\\ II \qquad 5 x -2 y = 1 \qquad / \cdot1\\ I \qquad -9 x +2 y =-5\\ II \qquad 5 x -2 y = 1 \\ \text{I + II}\\ I \qquad -9 x +5 x+2 y -2 y =-5 +1\\ -4 x = -4 \qquad /:\left(-4\right) \\ x = \frac{-4}{-4} \\ x=1 \\ \text{x in I}\\ I \qquad 9 \cdot 1 -2y =5 \\ -2 y +9 =5 \qquad / -9 \\ -2 y =5 -9 \\ -2 y =-4 \qquad / :\left(-2\right) \\ y = \frac{-4}{-2} \\ y=2 \\ L=\{1/2\} \end{array} \end{array} $